Mitochondrial DNA Polymorphism of the European Roe Deer, Capreolus capreolus (Artiodactyla, Cervidae), from the South-West of Ukraine - Zvychaynaya, E.Y.; Volokh, A.M.; Kholodova, M.V.; Danilkin, A.A. (Вестник зоологии, 2013)
Analysis of mtDNA control region (934 b. p.) and cytochrome b gene (1140 b. p.) polymorphism of the 33 roe deer samples from the south-west of Ukraine was carried out. 30 different haplotypes of mtDNA have been described and all of them are related to Capreolus capreolus Linnaeus, 1758. Two well differentiated haplogroups were discovered on the examined territory. The isolated subgroup of related haplotypes was revealed in the Crimea that is likely a result of the long-term geographical isolation of the Crimean roe deer populations.